Moderating role of board gender diversity between odd board composition and audit quality - Muhammad Zia Ul Hassan; S. M. Labib Abdul Baith; Jahanzaib Safdar Butt; Asad ul Islam Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
This study investigates the relationship between odd board structure, board gender diversity, and audit quality in Pakistani firms. The data is collected from Pakistan Stock Exchange's KSE100 index companies from the year 2016 to 2020. The study employs regression models to analyze the impact of an odd board structure on audit quality, as measured by audit fees. Additionally, the moderating role of board gender diversity on this relationship is examined. The findings reveal that an odd board structure positively influences audit quality, indicating that firms with an odd number of directors pay higher audit fees. However, the study could not find a significant moderating role of board gender diversity. The study recommends the adoption of an odd board structure to enhance audit quality and further emphasizes the importance of promoting board gender diversity to strengthen governance practices especially audit quality in the Pakistani context.
Keywords: 330; Voting model; even board; odd board; gender diversity; corporate governance; agency theory; audit quality and Pakistan stock exchange